2011
DOI: 10.1007/s00417-011-1677-x
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of low- and high-dose insulin on ROS production and VEGF expression in bovine retinal microvascular endothelial cells in the presence of high glucose

Abstract: High-dose insulin-induced ROS production and VEGF expression in BRECs in the presence of high glucose might be one of the reasons for the transient worsening of diabetic retinopathy during intensive insulin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In addition this finding was also similar as previous study by our group which demonstrated that diabetic BM-EPC has higher expression of fetal liver kinase-1 (Flk-1 or VEGFR2) [14]. Although the expression of VEGFR2 was significantly higher in diabetic BM-EPC, however in this study we did not rule out whether this transcript [53]. Therefore lack of insulin (as a common consequence of type-1 diabetic model due to deleterious effect of STZ on beta cell islet) may also contribute to the less expression of VEGF in diabetes.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In addition this finding was also similar as previous study by our group which demonstrated that diabetic BM-EPC has higher expression of fetal liver kinase-1 (Flk-1 or VEGFR2) [14]. Although the expression of VEGFR2 was significantly higher in diabetic BM-EPC, however in this study we did not rule out whether this transcript [53]. Therefore lack of insulin (as a common consequence of type-1 diabetic model due to deleterious effect of STZ on beta cell islet) may also contribute to the less expression of VEGF in diabetes.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…These results support an involvement of Nox4-derived ROS in insulin-induced angiogenesis in vitro . In fact, Nox4 has been associated with angiogenesis, overexpression of Nox4 was sufficient to promote endothelial proliferation, migration, and tube formation [6]. A recent study has shown that Nox4 (−/−) mice exhibited attenuated angiogenesis, further confirming the important role of Nox4 in angiogenesis [38].…”
Section: Discussionmentioning
confidence: 93%
“…Insulin-induced VEGF expression has been reported to be mediated through the activation of PI 3-kinase/AKT and p44/42 MAPK pathways, and hypoxia-inducible factor-1α (HIF-1α) [2]. Insulin has been shown to increase intracellular reactive oxygen species (ROS) production in many cell types such as HepG2 cells [3], 3T3L1 adipocytes [4], human fibroblasts [5], and retinal microvascular endothelial cells [6]. ROS produced by insulin are involved in HIF-1α and VEGF expression [3], [7].…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro study, insulin was found to increase reactive oxygen species (ROS) in bovine retinal endothelial cells. This increased insulin‐induced ROS production and VEGF expression, in the presence of high glucose, may explain early worsening DR (Table ) …”
Section: Theories Concerning the Paradoxical Early Worsening Of Drmentioning
confidence: 99%